2018
DOI: 10.1021/acs.biomac.8b00340
|View full text |Cite
|
Sign up to set email alerts
|

Processive Degradation of Crystalline Cellulose by a Multimodular Endoglucanase via a Wirewalking Mode

Abstract: Processive hydrolysis of crystalline cellulose by cellulases is a critical step for lignocellulose deconstruction. The classic Trichoderma reesei exoglucanase TrCel7A, which has a closed active-site tunnel, starts each processive run by threading the tunnel with a cellulose chain. Loop regions are necessary for tunnel conformation, resulting in weak thermostability of fungal exoglucanases. However, endoglucanase CcCel9A, from the thermophilic bacterium Clostridium cellulosi, comprises a glycoside hydrolase (GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…In contrast, the occurrence of X2 modules in free enzymes is particularly rare. To our knowledge, only one other free GH9‐enzyme from the thermophile Clostridium cellulosi was reported to display (three) X2 modules and characterized. In this recent study, it was suggested that these modules are essential for the endoprocessive mode of action of the enzyme since they help the C‐terminal CBM3b that this cellulase also displays, to strip out a single cellulose chain from the crystalline region of the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the occurrence of X2 modules in free enzymes is particularly rare. To our knowledge, only one other free GH9‐enzyme from the thermophile Clostridium cellulosi was reported to display (three) X2 modules and characterized. In this recent study, it was suggested that these modules are essential for the endoprocessive mode of action of the enzyme since they help the C‐terminal CBM3b that this cellulase also displays, to strip out a single cellulose chain from the crystalline region of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The mode of action of the Cel9A and Cel9G variants was also evaluated on amorphous cellulose as formerly described from the ratio soluble versus insoluble reducing extremities generated by the enzymes within 20 min of incubation. The data (Table ) indicate that, in contrast to the cellulase from C. cellulosi exhibiting a quite similar architecture, removal of the various C‐terminal modules of Cel9A (or grafting an R. cellulolyticum dockerin) did not have a significant effect on the mode of action of the L. phytofermentans cellulase, since all engineered forms of Cel9A globally conserve an endoprocessive mode of action, as revealed by ratios ≥ 1.5 (Table ). It should, however, be noticed that for C. cellulosi cellulase, different procedure (16 h‐incubation time at 60 °C) and substrate (filter paper) were used to investigate its processivity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the cellulase mixture gets in contact with cellulose, endo-cellulases and exo-cellulases bind specifically to it, due to the presence of a cellulose-binding domain (CBD) in their structure. Cellulolytic enzymes have specific domains that allows them to interact with cellulose [108]. Chu et al demonstrated that the selective removing of β-glucosidase activity in a corncob residue manages to double cellooligosaccharide production in a subsequent enzymatic hydrolysis, leading to an increase in COS yield (from 0.15 g/g to 0.25 g/g, corresponding at final concentration of 7.6 g/L and 12.6 g/L, respectively) and selectivity (from 30 to 60%) [109].…”
Section: Enzyme Name Enzyme Commission Number Activity Productmentioning
confidence: 99%
“…In addition, cellulases have been classified as processive or nonprocessive according to their mode of action on the substrates . Processive cellulases can slide along the cellulose chain after the initial hydrolysis step and continuously perform multiple rounds of catalysis before dissociating from the cellulose chain, whereas nonprocessive cellulases interact with a cellulose chain once, and then detach and interact with another cellulose chain . All microorganisms, by using cellulose as a carbon source, produce cellulases to efficiently degrade cellulose.…”
Section: Introductionmentioning
confidence: 99%